GreCo: An Energy Aware Controller Association Algorithm for Software Defined Networks - Ruiz-Rivera, A.; Chin, K.; Soh, Sieteng (IEEE Communications Society, 2015)
Software Defined Networks (SDNs) separate the control and data planes of devices to expedite the deployment, configuration and evolution of networks. In this respect, controllers play a key role. In particular, they control the behavior of switches and must do so quickly. This, however, may be at odds with the goal of reducing the energy consumption of a SDN because powering down links may cause controllers to use paths with larger propagation delays. To this end, we address the problem of assigning switches to controllers with the aim of switching off the maximum number of links subject to the following constraints: delay, link and controller load. Experimental results over four well known topologies show energy savings of up to 55% during off peak times.